Towards enhanced Museum Services: The application of Artificial Intelligence at the Louvre museum, Abu Dhabi - Kabata, Victor (Revue électronique suisse de science de l’information (RESSI), 2025)
This study sought to establish the extent to which the Louvre, Museum Abu Dhabi (the largest museum in the Arabian Peninsula) has deployed artificial intelligence tools to enhance its operations. Firstly, the study sought to identify the various AI tools that can be implemented in a museum setting. Subsequently, the study explored ways through which the identified AI tools were deployed to enhance museums’ work processes and operations. Thirdly, the study provides an analysis on which of the identified AI tools have been implemented at the Louvre Museum, Abu Dhabi. Lastly, the study will make recommendations on how museums across the world can optimize AI technologies to embed a digital museum experience. The study adopted a qualitative research approach and a case study research design where the Louvre Museum, Abu Dhabi is the main case. Data was collected through literature review and semi structured interviews. Specifically, to answer research question 1, 2 and 4 of the study, data was collected by reviewing books and journal articles relating to digital technologies in museums. For research question 3, the researcher reviewed literature relating to the operations of the Louvre Museum, Abu Dhabi as well as interviewed one of the staff at the museum familiar with the implementation of AI technologies. Data was analysed thematically based on the research questions of the study.